Rapid and simple method for simultaneous determination of escin and diethylamine salicylate in pharmaceutical preparations by partial least-squares multivariate calibration - Donmez, Ozlem Aksu; Bozdogan, Abdurrezzak; Kunt, Gonuel (SPRINGER WIEN, 2006)
A partial least-squares calibration (PLS) method has been developed for simultaneous quantitative determination of escin (ES) and diethylamine salicylate (DAS) in pharmaceutical preparations. The resolution of these mixtures has been accomplished without prior separation or derivatisation, by using partial least-squares (PLS-2) regression analysis of electronic absorption spectral data. The experimental calibration matrix was constructed with 9 samples. The concentration ranges considered were 10, 20, 30 (ES) and 40, 50, 60 (DAS) mu g cm(-3). The absorbances were recorded between 200 and 325 nm every 5 nm. Proposed method was compared with conventional spectrophotometric method. The results show that PLS-2 is a simple, rapid, and accurate method applied to the determination of these compounds in pharmaceuticals.
Keywords: spectrophotometry; multivariate calibration; escin; diethylamine salicylate; SPECTROPHOTOMETRIC DETERMINATION; QUANTIFICATION; NICOTINATE; REGRESSION; CAFFEINE; AESCIN; Chemistry